Relationship between the number of breaths that maximizes heart rate variability and height in patients with incurable cancers - Hideaki Hasuo; Hideki Ishikawa; Hiromichi Matsuoka (Elsevier, 2021)
Introduction: Resonant frequency breathing is a coping skill used for relaxation. A resonant frequency varies from person to person and is only investigated by specialized medical institutions. Methods: The relationships between patients' resonant frequencies and age, sex, height, and body weight were assessed using an analysis of variance. Results: The average resonant frequency among the 50 patients with incurable cancers was 6.05 breaths per minute. There was a significant difference in height between the resonant frequencies of 5, 5.5, 6, 6.5, and 7 breaths per minute (p < 0.001). Conclusion: Resonant frequency may be correlated with height in patients with incurable cancers. Trial registration: UMIN000029820. Registered on November 4, 2017.